ANTESEDEN DAN KONSEKUEN PENGGUNAAN MEDIA SOSIAL BAGI UMKM: ANALISIS PERSPEKTIF ORGANISASI - Anissa Hakim Purwantini; Friztina Anisa (Jurnal Ekonomi dan Bisnis, 2018)
Utilization of social media technology for business interests has been widely done both in largecompanies and MSMEs (Micro, Small and Medium Enterprise). Utilization of social media forMSMEs is very important to face the competition in this globalization era. This study empiricallyexamines the antecedents of social media usage and its impact on MSMEs performance basedon the Technology-Organization-Environment framework and Resource Based View theory. Thesurvey method by distributing questionnaires was conducted to MSMEs from various industriesin Magelang. Analysis with SEM-Partial Least Square indicates that customer pressure andmobile environment are significant factors affecting the use of social media. Furthermore, thedimensions of the impact on internal operations, sales, marketing and customer service aresignificant and make the value of social media usage for MSMEs. Technological competenceand competitive pressure does not affect the social media usage for MSMEs.Keywords: social media, SMEs, organization perspective, TOE, RBV